The Correlation Between Reading Strategies And Reading Achievement - Waqiatul Munawaroh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading is a way of thinking process and learning. It gives a unique opportunity to explore ideas and acquire information. In achieving maximum results in reading, strategies are needed to support better results. Strategy is a general plan of action to achieve short, middle and long-term desired goals. Therefore, reading strategies are important to facilitate the reading process. In this study, the researcher chooses B class to be the participants. The participants of this research were 20 students of the sixth semester of English Department of University Islam Malang. The data analyzed by using descriptive quantitative research and Pearson product moment coefficient correlation in SPSS ver.20 to find the correlation between reading strategies and reading achievement. In investigating this study, the researcher used questionnaire from Fauzan (2014) and reading final score from Reading IV lecturer as the instruments for collecting the data. The finding represented that there is positive correlation between reading strategies and reading achievement. The significance value calculated 0.454 is smaller than 0.05 (P-value = 0.044 < 0.05). Means that, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that there is positive correlation between reading strategies and reading achievement. In conclusion, 20 students from B class at the sixth semester are students who actively used reading strategies, the more students use reading strategies the higher their reading achievement. Reading strategies can help students overcome difficulties in reading and improve their reading achievement.Keywords:Â Correlation, Reading Strategies, Reading Achievement